The Need for Analyzing Collective Agreements in Canada - Quinet, Félix (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1967)
In this article, the author explains the reasons why a thorough analysis of collective agreements must be undertaken. These documents are subjected to environmental factors and generate changes. Moreover, they are related to and influenced by broad economic and social policies and objectives. He also investigates some technical problems involved in the analysis of collective agreements.